THE EUROPEAN LABOUR MARKET AND ITS CHANGES - Kotynkova, Magdalena (European Scientific Journal, ESJ, 2015)
Since the 70s of the last century European labour market has passed gradual changes which are connected with consequences of industrial era dominating in Europe since the second half of the 19th century. Progressive implementation of labour-saving technologies, information and telecommunication technologies changed economic activity and consequently the labour market. The structure and character of economic activity and afterword contents and forms of work were changed as well. The accompanying phenomenon of these changes in the labour market was growing uncertainty and the level of unemployment which have been becoming a commonly solved problem of the EU countries since the 90s. The goal of the paper is to outline basic trends in the development of current changes in the labour market including new forms of the labour market both regarding the content of work and its forms and possibilities of job creation outside private and public sector, namely within social economy.